Perspectives of Architects on Obstacles of Sustainable Architecture in Metropolitan Areas of Iran - Salek Zamankhani, Jalal (European Journal of Sustainable Development, 2018)
In the era of ecological and economic crises all over the world, while the trend has drastically changed, most buildings in the developing countries are still built in a conventional way. The problem has roots in the fact that ecologically sustainable buildings are often initially challenging in design process and more costly compared to ordinary ones. On the other hand, there has been little research discussing the impact of sustainable architecture trend on real estate benefits and marketing of the buildings. Yet a lack of research investigating the importance of architecture in the marketplace of sustainable or green buildings especially high-rise ones is evident. This study presented current literature on sustainable architecture and an analysis of the building appraisal process in different locations and mainly in Iran with special attention to the perspective of architects active in high-rise construction. Keywords: architect, building, green, sustainable.